City networks : collaboration and planning for health and sustainability - Karakitsiou, Athanasia ; Migdalas, Athanasios ; Rassia, Stamatina Th ; Pardalos, P. M. (Springer, 2020)
Sustainable development within urban and rural areas, transportation systems, logistics, supply chain management, urban health, social services, and architectural design are taken into consideration in the cohesive network models provided in this book. The ideas, methods, and models presented consider city landscapes and quality of life conditions based on mathematical network models and optimization. Interdisciplinary Works from prominent researchers in mathematical modeling, optimization, architecture, engineering, and physics are featured in this volume to promote health and well-being through design. Specific topics include: - Current technology that form the basis of future living in smart cities - Interdisciplinary design and networking of large-scale urban systems - Network communication and route traffic optimization - Carbon dioxide emission reduction - Closed-loop logistics chain management and operation - Modeling the effect urban environments on aging - Health care infrastructure - Urban water system management - Architectural design optimization Graduate students and researchers actively involved in architecture, engineering, building physics, logistics, supply chain management, and mathematical optimization will find the interdisciplinary work presented both informative and inspiring for further research. Smart Cities Enabling technologies for future living (P. Wlodarczak) -- City Networking in Urban Strategic Planning (F. Fontana) -- Network in Smart Cities from a Graph Theoretic Point of View (M. Haddad) -- An Evaluation of Measures for the Reduction of Carbon dioxide Emissions from Automobile Traffic in Central Tokyo (K. Yamamoto, K. Shen). -- Using Social Media Data to Infer Urban Attitudes about Bicycling: An Explanatory Case Study of Washington DC (J. Hollander, Y. Shen). -- Sustainable Mobility (F. Kehagi) -- Sustainable Operation of Closed-loop Logistics Chain from an Economic and Environmental Performance Perspective (B.Y. Liu, H.D Yang) -- Bridging borders: integrating data analytics, modeling, simulation and gaming for inter-disciplinary assessment of health aspects in city networks (J. Raghothama, E. Moustaid, V.M. Shreenath, S. Meijer) -- Ageing in the Contemporary Urban Context: The Case of Older Residents in Genoa (M. Palumbo, S. Poli) -- A Multicriteria Ranking of Thessaloniki's Public Hospitals Based on Their Infrastructure Adequacy (G. Chatzipoulidis, G. Aretoulis, G. Kalfakakou) -- Sustainable urban living and social capital(I. Daskalopoulou) -- Power distribution network planning optimization in smart cities (V. Dumbrava, T. Miclescu, G.C. Lazaroiou) -- Sustainable urban water management (A. Zafirakou) -- Introduction to Architectural Design Optimization (T. Wortmann and G. Nannicini).